ANALISIS PENGEMBANGAN UMKM SIRUP BUAH MANGROVE DI MANGUNHARJO SEMARANG - Bahiyah, Khoridatul; Hidayatullah, Ahmad Fauzan (Universitas Gorontalo, 2024)
Mangunharjo Village is included in one of the areas on the west coast of the city of Semarang which has various types of mangrove trees. Lack of public knowledge about the benefits of mangrove fruit, so that ripe mangrove fruit on the tree is left alone until the fruit falls into the water. From this it is necessary to have the utilization of pedada fruit. This study aims to determine the factors that can cause bacada fruit in the Mangunharjo area to not grow back after land leveling using heavy equipment. The method used in this research is descriptive qualitative. Data collection was carried out by means of literature studies and interviews. The results of the research show that in the Mangunharjo area there have been no pedada fruits since the 1980s. This was due to land clearing for building buildings. The head of the mangrove processing group has also never produced mangrove fruit syrup because if you want to make mangrove fruit syrup you have to take broiler fruit from the Demak area. The head of the mangrove group had only had training in making mangrove syrup but did not produce it. There are several factors that cause the soil resulting from land leveling to be infertile or unable to be planted with plants, one of which is due to soil acidity. In addition, the government's attention to mangrove processing is also lacking.Keywords: Mangrove Fruit, Soil Damage, Syrup, Marketing Strategy